2018
DOI: 10.1155/2018/8964027
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Microvascular Complications of Diabetes in a High-Risk Middle East Population

Abstract: Aims Much of the diabetes burden is caused by its complications. This cross-sectional study aimed to determine the prevalence and risk factors for diabetic microvascular complications (retinopathy, nephropathy, and neuropathy) in a high-risk population. Methods We collected information via a structured questionnaire and directly from the patient's record on 1034 adult type 2 diabetic patients who were attending outpatient clinics in Qatar. Results The mean age of the patients was 55 ± 10 years, and the mean du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
39
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 24 publications
6
39
1
11
Order By: Relevance
“…Among 100 patients have been recruited in the study, diabetic patients with nephropathy was (14%). Near to (15.3%) mentioned in the the study of Sohaila Cheema et al [13] .…”
Section: Discussionmentioning
confidence: 81%
“…Among 100 patients have been recruited in the study, diabetic patients with nephropathy was (14%). Near to (15.3%) mentioned in the the study of Sohaila Cheema et al [13] .…”
Section: Discussionmentioning
confidence: 81%
“…Our report agrees with other studies. Age at onset of diabetes was strongly associated with an increasing number of complications 36. In other regions, studies that have looked at the age of onset of diabetes have found that early onset diabetes increases disease severity.…”
Section: Discussionmentioning
confidence: 97%
“…The goals of caring for patients with type 2 diabetes mellitus are to reduce symptoms and to prevent, or at least slow down, the development of complications [ 10 ]. Glucose control in these patients undoubtedly has benefits for major microvascular endpoints; good glucose control does improve microvascular disease and should be achieved early and maintained over as long a period of time as possible [ 11 , 12 , 13 , 14 ]. On the other hand, early prediction of the signs of DPN through signal-analysis methods is urgently needed by diabetic patients and clinic doctors.…”
Section: Introductionmentioning
confidence: 99%